Continuous quadratus lumborum type 3 block provides effective postoperative analgesia for hip surgery: case report - Yayik,Ahmet Murat (2019)
Abstract Introduction: Hip surgery is a major surgery that causes severe postoperative pain. Although pain during rest is usually considerably reduced mobilization is important in terms of thromboembolic complications. The quadratus lumborum block is a regional analgesic technique that blocks T6-L3 nerve branches. This block may provide adequate analgesia and reduce opioid consumption after hip surgery. Case report: We performed continuous quadratus lumborum type 3 block in two patients who underwent hip arthroplasty. Postoperative 24-h pain scores, local anesthetic consumptions on patient-controlled analgesia and additional analgesic requirement were recorded. In two patients, postoperative pain scores were less than 6 during rest and physiotherapy. Patient was mobilized in the early postoperative period without additional opioid analgesic requirement and without muscle weakness. Discussion: Continuous quadratus lumborum block may be used to relieve postoperative acute pain in hip surgery because it provides one-sided anesthesia without muscle weakness.